A taphonomic analysis of the ungulate fauna from the early Howiesons Poort at Klasies River site - Achieng, Pamela Akuku (My University, 2019)
The Howiesons Poort (HP), a key Middle Stone Age techno-complex investigated by several recent studies in South Africa, is characterized by innovative lithic reduction techniques and projectile weapons hinting at human behavioural complexity in the Late Pleistocene. This complexity is also evident in the 1.8 metre HP sequence from Klasies River main site (KRM). The subsistence behaviours and occupational activity at KRM has received much less attention than the lithic technology, leading to an underdeveloped understanding of behavioural complexity of the HP at KRM. In this study taphonomic analyses, a crucial step in establishing subsistence strategies and site formation processes, have been undertaken for two layers from the lowermost HP deposits in Cave 1A, from square J51 layers YSx5 and CPx4. The relatively high incidence of acid etching, weathering, tooth marks and low degree of burning and cut marks suggest both human and carnivore accumulators in layer YSx5. Layer CPx4 on the other hand records relatively higher levels of burning, percussion marks and cut marks indicating human accumulators. The higher levels of trampling and abrasion in CPx4 indicates a period of higher occupational intensity while the lower levels of acid etching, tooth marks and weathering indicate lower carnivore activity as well post depositional exposure of bone. The abundance of the bovid size classes varies in the two layers with YSx5 exhibiting a prevalence of size 1(0-23kg) and CPx4 exhibiting size 2 (23 86kg). This most likely signifies variation in subsistence strategies with larger size classes showing higher degrees of human modification.
A research report submitted in partial fulfilment of the requirements of the Degree of Masters of Science in Archaeology, School of Geography, Archaeology and Environmental Studies to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2019
Keywords: Archaeology--South Africa; Mesolithic period; Human evolution